(3JMQjV GdENhGf GdcQGe hHPd GdfUjMI aj GdJMQR ef jCe GddFGe hCaYGdge GdbHjMIs - (3GdMSjf Hf eMeO Hf GdMSjf GdGHQjbj GdMHGfj GdMVQejs ((3eMeO Hf SYjO GdSdai s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdSja ef CYXe CSHGH EbGeI Ojfg Gdbhje , hMK Ydi GdLgGO ai YOI BjGJ ef cJGHg GdeLjO GdcQje s
(3BNQgG (B:s
(3hESJZaQ Gddg GdYXje di hdhGdOi hddeDefjf hGdeDefGJ hGdeSdejf hGdeSdeGJ JeJ GdQSGdI HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B8s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjjf hHYV GdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3GdJaSjQ hYdhe GdbQBfs